Investigation tetranuclear complexes of iron (II) by Mössbauer spectroscopy - Kassenova, N.B.; Yerkassov, R.Sh.; Baisalova, G.Zh. (KSU Publ., 2014)
A series of Fe (II) complexes, {[(tpma)Fe(-CN)]4}X4 (X = ClO4 –, BF4 –, and PF6 –; tpma = tris(2-pyridylmethyl) amine) were prepared by reacting the {Fe(tpma)}2+ building block with (Bu4N)CN. All three complexes exhibit gradual temperature-driven spin crossover (SCO) associated with the high-spin (HS)  lowspin (LS) transition at two out of four metal centers. The evolution of HS and LS Fe (II) ions with temperature was followed by a combination of Mössbauer spectroscopy.
Мёссбауэр спектроскопия əдісімен төртядролы темір (II) комплекстерін зерттеу
Исследование тетраядерных комплексов железа (II) методом Мёссбауэровской спектроскопии
Keywords: spin-crossover; Fe (II) complexes; Mössbauer spectroscopy